2015
DOI: 10.1111/bph.13136
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and pharmacology

Abstract: Recent advances in the understanding of gene regulation have shown there to be much more regulation of the genome than first thought, through epigenetic mechanisms. These epigenetic mechanisms are systems that have evolved to either switch off gene activity altogether, or fine-tune any existing genetic activation. Such systems are present in all genes and include chromatin modifications and remodelling, DNA methylation (such as CpG island methylation rates) and histone covalent modifications (e.g. acetylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In our dual luminescence reporter test system, the HDAC inhibitors shared similarities but also showed distinct features. Consistent with the role of histone acetylation in epigenetic regulation (Stefanska and MacEwan 2015; Varela et al 2013), all HDAC inhibitors led to some degree of enhanced reporter activity. However, distinct features were the preferential effects in either ESCs as compared to neurons.…”
Section: Resultssupporting
confidence: 70%
“…In our dual luminescence reporter test system, the HDAC inhibitors shared similarities but also showed distinct features. Consistent with the role of histone acetylation in epigenetic regulation (Stefanska and MacEwan 2015; Varela et al 2013), all HDAC inhibitors led to some degree of enhanced reporter activity. However, distinct features were the preferential effects in either ESCs as compared to neurons.…”
Section: Resultssupporting
confidence: 70%
“…A growing number of data confirmed that microRNAs play a crucial role in the regulation of gene expression via control of post-transcriptional mRNA function. As “global-regulators” miRNAs direct a diverse range of cellular responses both in normal and pathological conditions [ 20 , 34 ]. Expression of miRNA is one of the universal epigenetic mechanisms implicated in the regulation of growth and survival pathways in cancer cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that epigenetic states can be disrupted by environmental factors and the importance of epigenetic alterations in human diseases is becoming increasingly evident [1][2][3]. Newer classes of drugs are being developed to regulate epigenetic mechanisms and counteract disease states [4]. DNA methylation is a well-studied epigenetic modification that has been associated with several human diseases including cancer, cardiovascular disease, rheumatoid arthritis and brain disease [5][6][7][8].…”
mentioning
confidence: 99%